Ideas for a Poetics of Intermedia - Whittington, Stephen (Australasian Computer Music Association Conference, 2006)
The author argues that intermediality is a metaphoric relationship between signifying systems. Transmediality is defined as the sharing of formal properties that are not specific to a single medium. The author offers suggestions for future study of the poetics of intermediality that goes beyond formalist poetics
Keywords: Intermédialité; transmédialité